Green credit policy and residents’ health: quasi-natural experimental evidence from China - Wang, Mengyu; Wang, Yichun; Guo, Bingnan (Frontiers in Public Health, 2024)
Background Residents’ health plays an important role in economic prosperity and national development. Methods The research analyzes data from 262 prefecture-level cities in China spanning the period from 2010 to 2021. Utilizing the implementation of green credit policy in China as a quasi-natural experiment, the paper employs the time-varying Differences-in- Differences (DID) model to evaluate the influence of green credit policy on residents’ health. Results The paper results show that: (1) the green credit policy significantly improves residents’ health, and this conclusion still holds after a series of robustness tests. (2) Mechanism analysis reveals that the green credit policy affects residents’ health through the improvements of the environment and the elevation of public services standards in demonstration cities. (3) Heterogeneity analysis shows that the impact of green credit policy on residents’ health is more significant in the western cities and resource-based cities than in the central-eastern cities and non-resource-based cities. This paper explains the specific path and realization of green credit policy to enhance residents’ health, which provides a reference for further designing and improving effective green credit policy. Discussion The deficiencies within the green credit policy has resulted in limited improvements. It is recommended that China should broaden the ambit of the green credit policy and refine the criteria for its execution.